Treatment of sulfidic spent caustic using catalytic wet air oxidation with pure granular activated carbon - Nuraainaa Diyana, Mohamed Zaidi; Noor Sabrina, Ahmad Mutamim (2021)
Wastewater sludge from refinery operations of petrochemical industry has become a problem for most companies due to its diverse range of contaminants such as sulfides, mercaptans, nitrogen dioxide etc. Essentially, sulfidic spent caustic is a very toxic waste that can be classified as reactive and highly corrosive because it contains sulfide, high chemical oxygen demand (COD), highly odorous caustic spent and respectively has a high pH value. Treatment of sulfidic spent caustic was proposed and investigated to be under catalytic wet air oxidation (CWAO) method with pure granular activated carbon which is more environmentalfriendly and low cost treatment system.